Implementasi Server Failover Pada Software Defined Network - Dea Asmara Gita; Sabriansyah Rizqika Akbar; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Client-Server architecture is an architecture in computer network which involves data exchanges between two devices, in this case client and server. The server role in Client-Server architecture is very important because the server has a task to provide services that required by the client. So, if the server is down, client can't access services that server provides. To solve this problem, we need a high availability system. Many high availability systems which have been built uses master and slave model. In this study, high availability system in Client-Server architecture is built using Software Defined Network technology. Software Defined Network is a network architecture that separates between control plane and data plane. We hope Software Defined Network has a controller which gives information of the network, so the failover process will be faster. We get results of 0.826 second on average downtime, 0.865 second on average failback time, and 5.6% packet loss rate on failover process.